The Effect of Work Motivation and School Climate on the Professionalism of Mathematics Teachers in SMAN Kota Pekanbaru - Marnita, Eva; Isjoni, Isjoni; Chairilsyah, Daviq (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
Teacher professionalism is one of the variables that determines the success of education in the future. Based on the results of observations, it is known that teacher professionalism is still low. This study aims to determine the effect of work motivation and school climate on teacher professionalism. This research was conducted in Pekanbaru City, Riau Province in 2024. The sample in this study was 130 Mathematics teachers. The sampling technique used simple random sampling with data collection techniques using questionnaires. The data analysis techniques used in this study were simple linear regression and multiple linear regression. Based on the results of the study, it is known: 1) There is an effect of work motivation on the professionalism of mathematics teachers at SMAN Pekanbaru City, 2) There is an effect of work climate on the professionalism of mathematics teachers at SMAN Pekanbaru City, 3) There is an effect of work motivation and work climate on the professionalism of mathematics teachers at SMAN Pekanbaru City. Based on the research results, the regression equation Y = 7.954 + 0.157 obtained the meaning that each unit increase in work motivation and school climate scores together can increase teacher professionalism scores by 0.157 and 0.661 respectively at a constant of 7.954. In this way, it can be said that the higher the work motivation and the better the school climate, the greater the degree of professionalism of Mathematics teachers at Pekanbaru State High School.